Introduction of Artificial Intelligence in the Justice System: International experience - Balynska, Olha; Barabash, Olha; Zabzaliuk, Dmytro; Shehavtsov, Ruslan; Stetsyuk, Nataliya (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of this study is to determine ways to introduce artificial intelligence into the Ukrainian justice system. [Methodology/Approach/Design] The methodological basis of the study consists of theoretical and specialised legal methods: philosophical approaches, general and special methods of modern legal science, which are to interpret the law, and also general scientific styles. [Findings] During the study, the features of the use of artificial intelligence in the justice system were established and an analysis of international experience in the use of artificial intelligence in the justice system was conducted, which allowed identifying positive and negative aspects in the practice of other countries. In addition, problems that may hinder the development of artificial intelligence in the justice system of Ukraine and positive trends in the introduction of this innovative communication technology were identified. Based on the identified disadvantages and advantages of using artificial intelligence in justice, it was determined which systems should be implemented in the Ukrainian justice system, in particular the ‘judge's companion’ system. However, it is evident that at the moment artificial intelligence cannot completely replace people.